Analysis of the risk present in the granting of agricultural loans in the Banco de Venezuela (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
The objective of the research was to analyze the risk present in the granting of agricultural credits in the Banco de Venezuela, Lara state, from 2012 to 2015, based on the approaches of Nava (2012) that define the fundamental principles of the risk system. From the methodological perspective, it is assumed as a quantitative and descriptive research, the design is non-experimental, using as a source of information collection a questionnaire applied to workers of the financial institution. Data analysis and interpretation was performed, presented in summary form using tables and matrices. It was determined that, if the bank manages the information and data of the applicant, the risk of credit operations can be minimized, allowing a lesser degree of uncertainty for decision-making, since such information is essential to evaluate, analyze and make a decision. Adequate decision without harming the client. It is recommended to deepen the knowledge in credit matters, being of vital importance for the organization to reach a level of knowledge according to the functions developed by the department, which contributes to minimizing the risk in the granting of agricultural credits
Keywords: risk system; agricultural credits; strategic banking guidelines